Preferensi Konsumen Terhadap Atribut Produk Minuman Olahan Buah Gumijus Cabang Tubagus Ismail - Salimah, Alya Izzati; Sadeli, Agriani Hermita; Noor, Trisna Insan; Pardian, Pandi (Universitas Galuh, 2025)
There are notable behavioral differences between online and offline consumers. Generally, consumers prefer to purchase food and beverages, including fruit-based smoothies, through offline channels. However, offline sales at the main Gumijus branch located in Tubagus Ismail have shown a decline. This research seeks to identify consumer characteristics and their preferences in purchasing Gumijus smoothies through offline channels, focusing on specific product attributes. A quantitative approach was employed, involving 100 respondents, with data descriptive and conjoint analysis methods. The results indicate that the majority of consumers are female, belong to Generation Z, are students or university students, hold a bachelor’s (S1/D4) degree, have an income of more than Rp4,482,915, and usually purchase smoothies 1–3 times a week. Most of them found out about Gumijus through family, friends, or acquaintances. The preferred smoothie combination among consumers includes a slightly sweet taste, thick texture, single-serving portion, health benefits that support the immune system, a price range of Rp15,000–Rp25,000, low sugar content, online advertisements, and a buy 1 get 1 promotion.